Economic analysis of the phase III MENSA study evaluating mepolizumab for severe asthma with eosinophilic phenotype. (4th March 2017) - Basu, Anirban; Dalal, Anand; Canonica, Giorgio Walter; Forshag, Mark; Yancey, Steven W.; Nagar, Saurabh; Bell, Christopher F.
ABSTRACT: Background : Severe eosinophilic asthma patients are at risk of exacerbations, which are associated with substantial costs. Mepolizumab lowers eosinophil levels and reduces exacerbation risk in severe eosinophilic asthma. We evaluated asthma-related exacerbation costs in mepolizumab-treated patients (versus placebo). Methods : A within-trial economic analysis of the Mepolizumab as Adjunctive Therapy in Patients with Severe Asthma (MENSA) trial. Objectives were to quantify the incremental: (1) medical costs of asthma-related exacerbation; (2) asthma-related exacerbation emergency department visit/hospitalization costs; and (3) asthma-related total healthcare resource utilization. Results : Mean medical costs of asthma-related exacerbations at 8 months were $969, $852, and $1692 in the mepolizumab 75 mg intravenous (IV), mepolizumab 100 mg subcutaneous (SC), and placebo groups, respectively (p = 0.16). Mean medical costs from emergency department visits or hospitalizations due to asthma-related exacerbations were $901, $795, and $1557 in the mepolizumab 75 mg IV, mepolizumab 100 mg SC, and placebo groups (p = 0.020). Asthma-related healthcare resource utilization (all services) was lower for the mepolizumab groups versus placebo. Conclusions : Adding mepolizumab to standard-of-care treatment for severe eosinophilic asthma lowered asthma exacerbation-related medical costs/healthcare resource utilization; although the cost savings ranged from $723–$840 per patient, differences were not statistically significant.